Cultivation-dependent and -independent approaches for determining the distribution of Fusarium oxysporum f. sp. cubense tropical race 4 in soil of banana plantations in Côte d'Ivoire. Issue 6 (2021) - Ouina, Toualy Serge; Rodrigue, Voko Bi Rosin Don; Gente, Stéphanie; Garon, David; Rioult, Jean-Philippe; Panoff, Jean-Michel; Koussémon-Camara, Marina
No abstract available